ANALISIS PENGARUH CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION DI RESTAURANT JOONGLA, BANDUNG - Laurina, Teffa Queenanda; Andari Tirtadidjaja (Journal of Innovation Research and Knowledge, 2024)
In the competitive food and beverage industry, maintaining customer loyalty is critical to the success of a restaurant. One of the main factors known to influence a customer’s decisions to return is customer experience This research aims to investigate the influence of customer experience on revisit intention at Restaurant Joongla Bandung, a famous restaurant in the city of Bandung. The research method used was a quantitative method by conducting a survey using a questionnaire to respondents who had previously visited Restaurant Joongla Bandung. Respondents were asked to provide their assesments of various aspects of the customer experience they experienced during their visit to the restaurant . This research is expected to provide a deeper understanding of how overall customer experience influences the intention to return to a restaurant, especially in the context of Restaurant Joongla Bandung. It is hoped that the findings from this research will provide valuable insight for restaurant management in improving customer experience and maintaining customer loyalty.